Egg Predation Risk Trigger Adult Hoverfly (Diptera: Syrphidae) to Avoid Laying Eggs in Patches Attended by Ladybird Larvae (Coleoptera: Coccinellidae) - Nugroho Susetya Putra; Hironori Yasuda (Jurnal Perlindungan Tanaman Indonesia, 2005)
Oviposition preference of a predatory hoverfly, Episyrphus balteatus on the presence of its potential predators, the ladybird larvae which are inflicted serious impacts on its eggs was examined in a non-choice test. Our results revealed that the biggest and the most aggressive species of ladybird, Harmonia axyridis caused the worst impact on hoverfly eggs by attacking and feeding on. The species and developmental stages of ladybird were attributed to the level of predation risk. We correlated the oviposition site selection by hoverfly females to the egg predation risk level inflicted by ladybird larvae. Hoverfly females laid the least number of eggs on the patches attended by the strongest competitor, the larva of H. axyridis, and tended to lay the highest number of eggs on colonies attended by the weakest competitor, the larva of Scymnus posticalis. In addition, the impact of the fourth instar larva of ladybirds was stronger than of the first instar larva.